Epidemiological analysis of Neisseria gonorrhoeae in the Federal Republic of Germany by auxotyping and serological classification using monoclonal antibodies. Issue 3 (June 1986) - Kohl, P K; Knapp, J S; Hofmann, H; Gruender, K; Petzoldt, D; Tams, M R; Holmes, K K
Abstract : We evaluated a new serological classification system for Neisseria gonorrhoeae based on monoclonal antibodies directed against epitopes on the outer membrane protein I, in conjunction with auxotyping, to analyse gonococci from two cities in the Federal Republic of Germany. Isolates of N gonorrhoeae were collected during 1976-8 and 1980-2 in Lübeck, and during 1980-2 in Heidelberg. Between the two study periods in Lübeck, we observed an appreciable decrease in strains of the auxotype that requires arginine, hypoxanthine, and uracil (AHU-) and with serovar class PrIA-1 and the emergence of strains with the proline requiring auxotype and PrIB-1 serovar class. Serovar PrIA-1 accounted for 89 (97%) of 92 strains with the AHU- auxotype as opposed to 12 (4%) of 297 strains with other auxotypes (p less than 0.0001). Disseminated gonococcal infection was associated with AHU-/PrIA-1 strains. Penicillinase producing N gonorrhoeae (PPNG) strains belonged to eight different auxotype and serovar classes, which indicated that different strains had been imported. Classification of strains of N gonorrhoeae by auxotype and serovar class permits analysis of temporal changes in gonococcal populations, and of migrations of gonococci between different geographical areas. Typing N gonorrhoeae, together with assessing antibiotic susceptibilities, may prove useful for further studies of the epidemiology and control of gonorrhoea.